A novel Approach to System Security using Derived Odor Keys with Weight Elimination Neural Algorithm (DOK-WENA) - Iskandarani, Mahmoud Zaki (Transactions on Engineering and Computing Sciences, 2014)
A novel security technique for network and data communication applications that makes use of odors as password generators is developed and tested. The developed system employs odor keys derived from an original key together with the original key to allow access to systems and networks. The used key combinations are initially unknown to the user, and if detected while in the transmission process, there is no way of being able to be emulated. The uniqueness of the developed system is that it is not necessary for an odor key to be an exact replica of the original, but to be derived from the original. This is a chemical encryption and encoding as the right key will not be detected by anyone since it is a derived version and not a match. Genetic Algorithm is used to emulate the chemical derivation and to make up for any margin of odor detection error and sensors tolerances.